Keys to The Gift A Guide to Vladimir Nabokov's Novel - Leving, Yuri (Studies in Russian and Slavic Literatures, Cultures, and History, 2011)
"Yuri Leving's Keys to The Gift: A Guide to Vladimir Nabokov's Novel is a new systematization of the main available data on Nabokov's most complex Russiannovel, The Gift (1934-1939). From notes in Nabokov's private correspondence to scholarly articles accumulated during the seventy years since the novel's first appearance in print, this work draws from a broad spectrum of existing material ina succinct and coherent way and provides innovative analyses. The first part of themonograph, "The Novel," outlines the basic properties of The Gift (plot, characters, style, and motifs) and reconstructs its internal chronology. The second part, "The Text," describes the creation of the novel and the history of its publication, public and critical reaction, challenges of English translation, and post-Soviet reception. Along with annotations to all five chapters of The Gift, the commentary provides insight into problems of paleography, featuring a unique textological analysis of the novel.